Integrated Supply Chain Quality Management and an Organizational Performance Insights: a two-stage PLS-SEM and Artificial Neural Network (ANN) approach - Fajar Rio Kusviansyah; Romadhani Ardi (Publikasi Indonesia, 2024)
To generate value and optimize profitability, building successful partnerships with supply chain organizations is essential. This can be accomplished through training models, knowledge transfer, and support from top management. The implementation of advanced management practices is crucial to achieving these goals. In this context, an integrated approach to quality management, logistics, and supply chain management (SCM) is fundamental. Thus, harnessing the synergy between Quality Management (QM) and SCM is vital to enhance and promote organizational performance. Additionally, this study examines the significance and relationship between knowledge transfer, supply chain management capabilities, and top management support for organizational performance using PLS-SEM and ANN approaches. Primary data were collected through questionnaires from 200 respondents working in the manufacturing industry in Indonesia. Statistical analyses were performed using PLS-SEM with SmartPLS 4.0, and ANN with SPSS. The results reveal that supply chain quality management practices and top management support positively impact and have a strong relationship with organizational performance. This study provides insights into the role of supply chain quality management in organizational performance, especially in developing countries like Indonesia. It aims to help all manufacturing companies enhance their organizational performance by optimally combining selected SCQM practices with a focus on organizational performance